Juror #2 [videorecording (Blu-Ray)] - Abrams, Jonathan A.; Hoult, Nicholas, 1989-; Collette, Toni; Simmons, J. K.; Messina, Chris; Basso, Gabriel, 1994-; Deutch, Zoey, 1994-; Yarbrough, Cedric, 1973-; Bibb, Leslie; Sutherland, Kiefer, 1966-; Mancina, Mark; Bélanger, Yves, 1960- (Warner Bros. Entertainment, 2025)
"Juror #2" follows family man Justin Kemp who, while serving as a juror in a high-profile murder trial, finds himself struggling with a serious moral dilemma one he could use to sway the jury verdict and potentially convict or free the accused killer.